Kajian Teknis Manajemen Stockpile Pada Area Exportable Transit Ore Terhadap Moisture content Bijih Nikel Di PT. Koninis Fajar Mineral Kabupaten Banggai, Provinsi Sulawesi Tengah - Afandi, Rian; Purnomo, Hendro; Pangacella Putra, Bayurohman (Retii, 2023)
PT. Koninis Fajar Mineral is a company engaged in nickel mining operating in Banggai Regency. In the nickel mining process, nickel is not sent directly to the smelter, but nickel is stored first in the stockpile. The nickel produced must comply with the demand and conditions desired by the smelter, the specifications for the request for smelter nickel content are Ni 1.8%, Fe 15-40%, moisture content (MC) <35%, and SiO2 <2.5%. This study focuses on moisture content levels. This study aims to analyze the potential for increased moisture contentlevels from various factors in stockpile management activities. The method used is to observe the stockpilemanagement process from the beginning of nickel being stacked until it is transported. Based on the results of research and observations made, there are several factors that have the potential to increase the moisture content of nickel piles. Factors causing an increase in the moisture content in the piles include the condition of the stockpile floors being unfavorable, not closing the piles when it rains, not optimally stacking the piles, and unfavorable ditch conditions. Efforts that can be made to maintain nickel quality so that moisture contentdoes not increase include repairing stockpile floors, covering piles using tarpaulin when it rains, maximizingstockpile maintenance and supervision, and repairing stockpile area ditches.